In defence of Canada : peacemaking and deterrence - Eayrs, James George, 1926- (Heritage., 1972)
Volume III of this outstanding history of Canada's defence and foreign policy is a study of Ottawa's thinking and decisions during the closing years of the Second World War and the opening years of the cold war. Eayrs presents both the events and the personalities who shaped these events.